Digitalisasi Layanan Laundry: Pengembangan Aplikasi Berbasis Web untuk Meningkatkan Efisiensi Operasional - Ria Pebrian Dini; Faris Rizky Ramadhan; Mia Rosmiati; Alip Lizal (Universitas Mercu Buana Yogyakarta, 2025)
The laundry business is currently experiencing significant growth as people's mobility increases. Busy daily activities make it difficult for many individuals to carry out the routine of washing clothes at home. This opens up great opportunities for the laundry business, especially in educational environments such as campus areas that have a high level of busyness. However, most operational processes of laundry businesses are still done manually, especially in recording transactions, resulting in an estimated 35-40% data error rate and significant delays in financial reporting processes. Despite the growing demand for digital solutions in service industries, there remains a significant gap in affordable, user-friendly laundry management systems specifically designed for small to medium-scale operations. To address these critical operational challenges, a website-based application called WhiteWave was developed to support the administration and management of laundry businesses. This application was built using the Laravel framework and utilizes the Aiven Console as a tool in database management, which provides ease of collaboration between developers. Based on comprehensive functionality and effectiveness testing, all features in the application run optimally according to development objectives, demonstrating a 98% user satisfaction rate and 60% improvement in operational efficiency. With this application, laundry business processes become more efficient, structured, and demonstrate minimal errors in managing operational data.